Att förebygga kompetensbrist : En studie av Luleå kommuns rekryteringsbehov under de kommande åren - Hedéen, Niclas (2012)
The organization of Luleå municipality is since 2010 undergoing a major generational change that places high demands on the municipality's recruitment efforts. The municipality's effort to meet the organization’s need for skilled personnel is of great value to the city’s ability to develop and operate in accordance with the municipal vision Luleå 2050. The purpose of this study is therefore to create an overall picture of Luleå Municipalitys need of competence, it also describes the demand of competence that the municipality's top three administrations have over the next five years. After that there are some suggestions on how to meet this need. The study was mainly conducted through interviews and profound literary work and was then supplemented by existing materials and secondary data.The analysis is based on the three ideal types that are emerging during the study. Each ideal type illustrates one of the top three administrations problems from three perspectives: Experience, Status and Competence. The Ideal types are described together with the previous research conducted around the area of Competence, and shows that there are several connections between the problems of the three administrations, despite the problems themselves are different from each other based on the three ideal types used. The analysis shows that all three administrations set formal requirements for competence. All the administrations experience that it is difficult to recruit despite the difference in demands in competence based on the three ideal types, which could be related to the municipality's status as an employer in the labor market.Keywords: Competence, ideal types, recruitment, Luleå municipality, generational Validerat; 20120613 (anonymous)